2012
DOI: 10.3389/fphys.2012.00334
|View full text |Cite
|
Sign up to set email alerts
|

Extrasynaptic Glutamate Receptor Activation as Cellular Bases for Dynamic Range Compression in Pyramidal Neurons

Abstract: Repetitive synaptic stimulation overcomes the ability of astrocytic processes to clear glutamate from the extracellular space, allowing some dendritic segments to become submerged in a pool of glutamate, for a brief period of time. This dynamic arrangement activates extrasynaptic NMDA receptors located on dendritic shafts. We used voltage-sensitive and calcium-sensitive dyes to probe dendritic function in this glutamate-rich location. An excess of glutamate in the extrasynaptic space was achieved either by rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 83 publications
(237 reference statements)
5
74
0
Order By: Relevance
“…Some studies have reported a role for non-synaptic NMDARs in various functions such as extrasynaptic inhibition [95], or dynamic range compression [96]. But, aside from presynaptic NMDARs [97,98], which are not addressed in this review, most studies have focused on the manifestations of extrasynaptic NMDAR activity such as tonic currents and SICs.…”
Section: Role Of Slow Inward Currents and Tonic Current In Physiologymentioning
confidence: 99%
“…Some studies have reported a role for non-synaptic NMDARs in various functions such as extrasynaptic inhibition [95], or dynamic range compression [96]. But, aside from presynaptic NMDARs [97,98], which are not addressed in this review, most studies have focused on the manifestations of extrasynaptic NMDAR activity such as tonic currents and SICs.…”
Section: Role Of Slow Inward Currents and Tonic Current In Physiologymentioning
confidence: 99%
“…The mean peak amplitude of the dendritic Ca 2þ signal at the synaptic stimulation site (figure 1b, patch, Ca 2þ region of interest-ROI) was 11.2 + 0.7% (DF/F), in the same sample of eight cells. Dendritic Ca 2þ signals were tightly restricted to the synaptic stimulation site as previously shown [5,8]. The synaptically evoked dendritic NMDA spikes were challenged with a potent antagonist of NR2C and D subunits, PPDA (2 mM).…”
Section: (D) Drugsmentioning
confidence: 99%
“…Receptor channels located outside the synaptic cleft may also contribute charge to dendritic spikes [5,[12][13][14]. Besides the afferent glutamatergic axons, glial processes may also release glutamate that contributes to the glutamate build up (glutamate threshold) required to bring a dendrite into an UP state, which in turn brings the cell body into an UP state [1,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations